The influence of water-repellent admixtures on the behaviour and the effectiveness of Portland limestone cement mortars. (May 2015) - Falchi, Laura; Zendri, Elisabetta; Müller, Urs; Fontana, Patrick
Abstract: Water-repellent mortars were prepared using different hydrophobic compounds as admixtures. Calcium and zinc stearates, silane/siloxane products (as liquid solution and powder) were mixed into limestone cement mortars for obtaining in-bulk water-repellent mortars suitable for building protection and resistant to the degrading action of water. The influences of the admixtures on the hydration and structure of the designed mortars were investigated by SEM, TG–DSC, FT-IR, XRD, and isothermal calorimetry. The effectiveness of these agents against water action was evaluated by using techniques and methods such as mercury intrusion porosimetry, water absorption tests and contact angle measurements. Siloxane products conveyed good water-repellent effectiveness, without strongly influencing the setting and hydration of the binder, while the zinc stearates slowed down the hydration reactions.